Analysis of Filmmaking Projects for the Mirrorliar Competition at Nihon Go Gakko - Maharani Patria Ratna; Makino Masanori; Lunarreza Suwandi (Diponegoro University, 2022)
This article results from a fieldwork practice conducted at Nihon Go Gakko located at 999-2 Kamata, Ito, Shizuoka, 414-0054, Japan. The fieldwork practice was conducted online for four months, from January 2021 to April 2021. This article aims to explain the process of making short films involving various parties from several countries during the pandemic era in Nihon Go Gakko, who will be entered in the Mirrorliar. The methods of observation, literature study and interviews were used to analyse. The process of making films as a result of this research is the development, production process, post-production and distribution. Meanwhile, the obstacles faced during the process of making short films are weather, time, cost, etc